2017
DOI: 10.1016/j.biopsych.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Oxytocin to Prevent Posttraumatic Stress Disorder Symptoms: A Randomized Controlled Trial in Emergency Department Patients

Abstract: Oxytocin administration early after trauma did not attenuate clinician-rated PTSD symptoms in all trauma-exposed participants with acute distress. However, participants with high acute clinician-rated PTSD symptom severity did show beneficial effects of oxytocin. Although replication is warranted, these findings suggest that oxytocin administration is a promising preventive intervention for PTSD for individuals with high acute PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 67 publications
2
107
0
1
Order By: Relevance
“…Evidence from studies in animals and in healthy and psychiatric human populations have shown that oxytocin administration may modulate glucocorticoid and autonomic stress reactivity (100, 101), dampen anxiety, and alter neural threat processing (102, 103). However after exposure to trauma, oxytocin administration showed detrimental effects increasing amygdala reactivity to fearful faces and decreasing amygdala-ventrolateral prefrontal functional connectivity (104). Moreover other studies indicate that the effects of a single oxytocin administration may differ from the effects of repeated administration; the latter may be required to achieve clinically relevant effects regarding the prevention of PTSD (104).…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…Evidence from studies in animals and in healthy and psychiatric human populations have shown that oxytocin administration may modulate glucocorticoid and autonomic stress reactivity (100, 101), dampen anxiety, and alter neural threat processing (102, 103). However after exposure to trauma, oxytocin administration showed detrimental effects increasing amygdala reactivity to fearful faces and decreasing amygdala-ventrolateral prefrontal functional connectivity (104). Moreover other studies indicate that the effects of a single oxytocin administration may differ from the effects of repeated administration; the latter may be required to achieve clinically relevant effects regarding the prevention of PTSD (104).…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…Neuroendocrinological targets include the hypothalamic peptide oxytocin (OXT). Currently, there is conflicting evidence whether or not early posttrauma administration of OXT could be effective in reducing PTSD-like symptoms in victims of recent traumatic experiences [3]. Furthermore, it is increasingly recognized that the prosocial and anxiolytic effects of intranasal OXT are moderated by context factors [4].…”
mentioning
confidence: 99%
“…a minimum score on a screening instrument). For example, three studies (Bryant et al, 2012; deRoon-Cassini et al, 2010; Jenewein et al, 2009) had a minimum hospital admission length (24–48 hours), and three studies (Bonne et al, 2001; Shalev et al, 2012; van Zuiden et al, 2017) had a minimum threshold or criterion for initial symptoms. These criteria screened for more severely injured or more symptomatic patients to be included in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Jerusalem Trauma Outreach and Prevention Study (JTOPS) had 296 out of 1996 participants randomly assigned to treatment groups that included cognitive behavioural therapy, escitalopram, and placebo (Shalev et al, 2012). The Amsterdam oxytocin study (van Zuiden et al, 2017) evaluated the preventive effect of oxytocin, and data included in the ICPP consisted of that study’s placebo group. Beyond available information regarding general study design, investigators have used various inclusion and exclusion criteria for recruitment (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation